Comparing COL7A1 gene expression in fibroblast cells of dystrophic epidermolysis bullosa patients with clinical responses to autologous fibroblasts transplantation - Eslami, Maryam; Golshanfard, Majid; Bajouri, Amir; Aghdami, Nasser; Mohammadi, Mahsa; Shafieian, Saeed; Memarsadeghi, Omeed; Seifalian, Alexander (Journal of Contemporary Medical Sciences, 2023)
Objectives: This clinical research aimed to establish autologous fibroblasts transplantation as a possible treatment for patients with DEJ. The COL7A1 gene expression was also evaluated. Methods: Six patients (3M and 3F), 4 with no recurrent wounds and 2 with recurrent wounds after surgery, and 15 healthy subjects were included in the study as controls. Quantitative real-time polymerase chain reaction (real-time PCR) analysis of the COL7A1 gene was performed using an oligonucleotide primer pair designed to amplify across the exon/exon junction. Results: The COL7A1 expression level was down-regulated at exons 26-27, 47-48, 96-97, and 116-117 in all patients′ fibroblasts compared with the healthy controls. However, the expression of the COL7A1 gene in the fibroblasts of the patients with a positive response to the treatment was not significantly changed compared with the patients with the poor response. (ClinicalTrials.gov NCT01908088) Conclusion: In this study the mRNA expression levels of COL7A1 were significantly less in the patients when compared with healthy controls. However the COL7A1 expression after autologous fibroblasts transplantation was not different between the two groups of patients, and further examination is needed to elucidate the mechanism of the treatment.